The Effects of distilled Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture on the Heart Rate Variability - Kim Hui-Jun; Song Beom-Yong; Yook Tae-Han (Korean Pharmacopuncture Institute, 2009)
Objective : This study was to investigate the effects of distilled Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture on autonomic nervous system with Heart Rate Variability(HRV). Purpose of the trial was to observe what influence distilled Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture have on the autonomic nervous system. Methods : 60 healthy male volunteers were divided into three groups which consist of two experimental groups such as Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture, and a control group. Study design was a randomized, placebo-controlled, double-blind clinical trial. 20 subjects in experimental group were injected distilled Cervi Pantotrichum Cornu Pharmacopuncture at GB21(Kyonjong), 20 subjects in other experimental group were injected distilled Zizyphi Spinosi Semen Pharmacopuncture and 20 subjects in control group were injected Normal Saline at G21(Kyonjong). One volunteer of each groups were excluded from analysis because of error during measuring HRV. At the end of the study 57 volunteers completed HRV analysis. HRV was measured by QECG-3:LXC3203(LAXTHA Inc. Korea) at P0, P1, P2, P3, P4, P5 and P6 and its time-course dependent change in each group was analyzed using paired t-test, and the difference of HRV fluctuation among two experimental group and a control was evaluated by one way ANOVA(p<0.05). Results : A. Time Domain Analysis 1. Analysis of Mean HRV, SDNN and Complexity After injection of distilled Cervi Pantotrichum Cornu Pharmacopuncture, Mean HRV was significantly decreased only at 20 minutes after injection. SDNN was significantly increased from 15 minute after injection. Complexity was significantly decreased only at 15 minute after injection. After injection of distilled Zizyphi Spinosi Semen Pharmacopuncture, Complexity was significantly decreased at 10, 15 and 30 minutes after injection. 2. Analysis of HRV index, pNN50 After injection of distilled Cervi Pantotrichum Cornu Pharmacopuncture, pNN50 was significantly decreased at 15, 20 and 25 minutes after injection. Compared with Normal Saline injection, distilled Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture showed significant difference on HRV index and pNN50 at 5 minutes after injection. B. Frequency Domain Analysis 1. Analysis of Ln(TP), Ln(VLF) After injection of distilled Cervi Pantotrichum Cornu Pharmacopuncture, Ln(TP) was significantly increased at 15 and 30 minutes after injection. Ln(VLF) was significantly increased at 10, 15 and 30 minutes after injection. After injection of distilled Zizyphi Spinosi Semen Pharmacopuncture, Ln(VLF) was significantly increased only at 30 minutes after injection. Compared with Normal Saline injection, distilled Cervi Pantotrichum Cornu Pharmacopuncture showed significant difference on Ln(TP) after 5 minutes of injection. Conclusions : Our results suggest that Cervi Pantotrichum Cornu Pharmacopuncture and Zizyphi Spinosi Semen Pharmacopuncture in healthy adult man tend to activate the autonomic nervous system and sympathetic nervous system compared to Normal Saline within normal range.